Selection Guide to Wearing Respirators According to Work Situations and On-site Applicability - Don-Hee Han (Elsevier, 2021)
Background: This study aims to introduce the formulation of the regulation for the selection of respirators for accident preparedness chemicals (APCs) according to chemical workplace situations and to determine on-site applicability. Methods: Workplaces were grouped into seven work categories, and APCs were classified into six groups to select adequate respirators. A survey was conducted to enhance the understanding of work situations and adequate respirators. The total number of subjects surveyed in 2018 was 201 managers and handlers, and that in 2019 was 91 handlers and 204 managers. Results: Adequate respirators were allocated to each cell using the matrix method. The study observed an overall lack of understanding of work situations, especially in the operation of open devices, which was the highest at 32.7%. Despite its implementation in 2015, 17.6% and 25.0% of the managers and APCs handlers, respectively, were unaware of the regulations for selecting respirators. Only 70.4% of the APCs handler wore respirators in compliance with regulations. Conclusion: The method for selecting respirators according to work situations using the matrix method is considered reasonable. Thus, this study suggests that the development of educational contents and reinforcing education should be essential steps to increasing awareness of regulations.